(3OQGSI GdNGeGJ GdPcjI hJWHjbGJgG ai eLGd GdJUeje GdUfGYi(B/s - (3cQje UGHQ eUWai s ([(3O(B.(3e(B]:s [(3O(B.(3f(B](3,s, 2012)
(3jMJhi edNU HGddZJjf GdYQHjI hGdGfLdjRjI (B.s
(3GdeQGLY ef U (B(206-217).s
(3QSGdI eGLSJjQ (B:(3cdjI Gdafhf GdJWHjbjI ,LGeYI MdhGf bSe GdJUeje GdUfGYi (B.s
Keywords: (3GdNGeGJ GdPcjI s -- (3GdefJLGJ GdUfGYjI (B.s